A one health approach to tackling AMR and why gender matters: findings from pastoralist communities in Tanzania - Barasa, Violet (Frontiers in Global Women's Health, 2024)
This paper focuses on the gendered risk of AMR in community settings, through a study of gender and social determinants of access to and use of antimicrobials in low-resource pastoralist settings in Tanzania. It is based on an ethnographic and mixed-methods study of access and use of antibiotics in 379 pastoralists in Naiti, Monduli district, and it finds that gender and age are significantly associated with the use of antibiotics without a prescription. Younger people aged 18-24 (both male and female) are more likely to use unprescribed antibiotics than older people. The paper proposes that gender needs to be integrated into One Health approaches to understand and address the risk of AMR in pastoralist settings.